2022
DOI: 10.1371/journal.pntd.0010598
|View full text |Cite
|
Sign up to set email alerts
|

Partial masculinization of Aedes aegypti females by conditional expression of Nix

Abstract: Background Aedes aegypti, the main vector of dengue, yellow fever, and other arboviruses thrives in tropical and subtropical areas around the globe putting half of the world’s population at risk. Despite aggressive efforts to control the transmission of those viruses, an unacceptable number of cases occur every year, emphasizing the need to develop new control strategies. Proposals for vector control focused on population suppression could offer a feasible alternative method to reduce disease transmission. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…japonicus Nix , transgenic Nix expression was significantly lower than the endogenous Nix as determined by ddPCR (Figure 7). It has been suggested that an enhancer may exist in the Nix coding region as the Nix promoter, when used to drive the expression of tetracycline transactivator (tTA), produced significantly less tTA transcripts than the endogenous Nix transcripts (Kojin, et al 2022). It is possible that the Ae.…”
Section: Resultsmentioning
confidence: 99%
“…japonicus Nix , transgenic Nix expression was significantly lower than the endogenous Nix as determined by ddPCR (Figure 7). It has been suggested that an enhancer may exist in the Nix coding region as the Nix promoter, when used to drive the expression of tetracycline transactivator (tTA), produced significantly less tTA transcripts than the endogenous Nix transcripts (Kojin, et al 2022). It is possible that the Ae.…”
Section: Resultsmentioning
confidence: 99%